Specialisation versus special interest - the Australian podiatry experience. - Davies, Ainslie; Bennett, Paul; Nancarrow, Susan; Cuesta-Vargas, Antonio (Wiley, 2015)
Background: Ensuring efficient and effective delivery of health care to an ageing population has been a major driver for a review of the health workforce in Australia. As part of this process a National Registration and Accreditation Scheme (NRAS) has evolved with one goal being to improve workforce flexibility within a nationally consistent model of governance. In addition to increased flexibility, there have been discussions about maintaining standards and the role of specialisation. This study aims to explore the association between practitioners' self-perceptions about their special interest in musculoskeletal, diabetes related and podopaediatric foot care and the actual podiatry services they deliver in Australia. Methods: A cross sectional on-line survey was administered on behalf of the Australasian Podiatry Council and its' state based member associations. Self-reported data were collected over a 3-week interval and captured information about the practitioners by gender, years of clinical experience, area of work by state, work setting, and location. Results: 218 podiatrists participated in the survey. Participants were predominately female and worked in private practices. The largest area of personal interest by the podiatrists was related to the field of musculoskeletal podiatry (n = 65), followed closely by diabetes foot care (n = 61), and a third area identified was in the management of podopaediatric conditions (n = 26). Conclusions: Health workforce reform in Australia is in part being managed by the federal government with a goal to meet the health care needs of Australians into the future. The recognition of a specialty registration of podiatric surgery and endorsement for scheduled medicines was established with this workforce reform in mind.
Keywords: Podología; Health workforce; Podiatry; Scope of practice; Specialisation; Substitution; Diversification